2023
DOI: 10.3390/drones7030220
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Technique for Photo-Identification of the Fin Whale, Balaenoptera physalus, as Determined by Drone Aerial Images

Abstract: Drones have become a crucial research tool across marine environments over the past decade, being specifically useful in marine mammal research. Fin whales (Balaenoptera physalus) have been monitored feeding along the Catalan coast, Spain (NW Mediterranean), since 2014. To overcome issues such as the distance between a whale and a research vessel or the lack of distinctive dorsal fin features, an aerial identification technique was developed. It uses the fin whales’ characteristic central chevron pattern (CCP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In this context, fast-paced technological advancements and analytical frameworks developed in recent decades are key tools for reducing these current knowledge gaps. The use of unmanned aerial vehicles (UAVs; [ 7 , 8 ]), environmental DNA (eDNA; [ 9 ]), remotely sensed imagery [ 10 ] and satellite-linked telemetry [ 11 , 12 ] has been critical in this regard, particularly within marine environments where regular observation would be otherwise logistically impractical.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, fast-paced technological advancements and analytical frameworks developed in recent decades are key tools for reducing these current knowledge gaps. The use of unmanned aerial vehicles (UAVs; [ 7 , 8 ]), environmental DNA (eDNA; [ 9 ]), remotely sensed imagery [ 10 ] and satellite-linked telemetry [ 11 , 12 ] has been critical in this regard, particularly within marine environments where regular observation would be otherwise logistically impractical.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [8] used a drone to research the waterbird populations, ungulates, and non-human primates. Degollada et al [10] identified fin whales (Balaenoptera physalus) using a drone. The authors in [11] used a drone to identify blacknecked swans (Cygnus melancoryphus).…”
Section: Introductionmentioning
confidence: 99%
“…As has already been reported in some species, UAVs play an essential role in cetacean ecological research, including individual identification (e.g., Degollada et al, 2023), body length or body condition estimation (e.g., Aoki et al, 2021;Stewart, 2021), behavioral observation (e.g., Amano et al, 2021;Hartman et al, 2020), and biopsy and microbiome sampling (e.g., Costa et al, 2022). Compared to boat surveys, UAVs generate significantly less noise in the water, making them less threatening to whales (Christiansen et al, 2016).…”
mentioning
confidence: 99%